2016
DOI: 10.17135/jdhs.2016.16.6.481
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Dementia and Oral Health in Some Elderly in Daejeon

Abstract: The elderly population with dementia is rapidly growing in South Korea. The aim of this study was to investigate the relationship between dementia and oral health in 197 subjects aged ≥65 years. The questionnaire included questions on subjective health status, subjective health concern, subjective oral health status and behavior, mastication ability, Oral Health Impact Profile-14 (OHIP-14), and Korean Dementia Screening Questionnaires (KDSQ). Oral examination was conducted by a single dentist to evaluate upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Other studies have also found that individuals with cognitive impairment have fewer remaining teeth than those without cognitive impairment 32 . However, in a study examining the relationship between dental health and dementia in the elderly using the Korean Dementia Screening Questionnaire 3,34 , neither the number of functional teeth, including implants and fixed prostheses, nor use of dentures had a significant effect on the risk of dementia, unlike in previous studies.…”
Section: Discussionmentioning
confidence: 65%
“…Other studies have also found that individuals with cognitive impairment have fewer remaining teeth than those without cognitive impairment 32 . However, in a study examining the relationship between dental health and dementia in the elderly using the Korean Dementia Screening Questionnaire 3,34 , neither the number of functional teeth, including implants and fixed prostheses, nor use of dentures had a significant effect on the risk of dementia, unlike in previous studies.…”
Section: Discussionmentioning
confidence: 65%
“…In addition to mental dysfunction due to simple brain function dementia, its symptoms are severely limiting interpersonal and social activities due to urinary problems and the difficulties of daily life. Also, [7] Dementia is a disease that causes a lot of pains for the patients and their families in the long-term and deteriorates the quality of life for all of them.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of dementia are markedly impaired in interpersonal relationships and social activities due to the difficulty of daily living, as the cognitive function of memory, judgment, reasoning, and computational ability is significantly decreased. [7] Dementia is a disease that causes long-term pain and poor quality of life for patients as well as those around them.…”
Section: Introductionmentioning
confidence: 99%